Patient Satisfaction in Out-patient Services at a Tertiary Care Center: A Descriptive Cross-sectional Study - Lisasha Poudel; Swechhya Baskota; Prajita Mali; Priza Pradhananga; Nabina Malla; Bibek Rajbhandari; Susmita Nepal (Journal of Nepal Medical Association, 2020)
Introduction: Patient satisfaction is an important and commonly used valid indicator for the measurement of service quality. Patient responses to healthcare services are one of the best ways to obtain information about patient views regarding the quality of healthcare. The main aim of the study was to find out the patient’s satisfaction level in the tertiary care center.